The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/jof3020017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Antifungal Susceptibility Patterns of Clinical Dermatophytes Following CLSI and EUCAST Guidelines

Abstract: Dermatophytes are associated with superficial infections in humans worldwide. The aim of the present study was to determine the species distribution and susceptibility patterns of clinical dermatophytes. Samples received for routine mycological processing from 124 suspected cases attending a dermatologic clinic in a tertiary care hospital were included in the study. On direct microscopy, 74.1% (92/124) were positive and 53.2% (66/124) grew on culture. The isolates were comprised of Trichophyton interdigitale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 33 publications
(39 reference statements)
8
45
2
3
Order By: Relevance
“…Previous worldwide studies as well as older Indian data report T. rubrum as the predominant dermatophyte causing tinea corporis/cruris, while T. interdigitale has previously been reported as a prominent species from only a few geographical areas (15)(16)(17)(18)(19)(20). However, a few recent Indian reports have also found T. interdigitale in a large percentage of isolates (9,10,21). Our results also reconfirm the unfortunate trend of high MICs of TRB for T. interdigitale.…”
Section: Discussionsupporting
confidence: 88%
“…Previous worldwide studies as well as older Indian data report T. rubrum as the predominant dermatophyte causing tinea corporis/cruris, while T. interdigitale has previously been reported as a prominent species from only a few geographical areas (15)(16)(17)(18)(19)(20). However, a few recent Indian reports have also found T. interdigitale in a large percentage of isolates (9,10,21). Our results also reconfirm the unfortunate trend of high MICs of TRB for T. interdigitale.…”
Section: Discussionsupporting
confidence: 88%
“…According to this most recently suggested classification and new taxonomy of dermatophytes, the former “ T mentagrophytes complex” is differentiated into T mentagrophytes (zoophilic strains) and T interdigitale (anthropophilic strains). We have noticed that in some recent studies the causative agent of the chronic, relapsing dermatophytosis outbreak in India has been described as T interdigitale . In our opinion, it is very likely that these T interdigitale strains isolated in Delhi and Chennai and other places in India are indeed strains more closely related to the neotype of T mentagrophytes and not strains of T interdigitale .…”
Section: Discussionmentioning
confidence: 81%
“…We have noticed that in some recent studies the causative agent of the chronic, relapsing dermatophytosis outbreak in India has been described as T interdigitale. 7,8,58,59 In our opinion, it is very likely that these T interdigitale strains isolated in Delhi and Chennai and other places in India are indeed strains more closely related to the neotype of T mentagrophytes and not strains of T interdigitale. 10 We therefore want to underscore the importance of a common nomenclature of species in accordance with the new taxonomy of dermatophytes.…”
Section: Trichophyton Interdigitale or Trichophyton Mentagrophytes?mentioning
confidence: 77%
“…24 Brazilian studies have revealed resistance of many strains to griseofulvin but in vitro antifungal susceptibility of dermatophytosis for the griseofulvin and terbinafine combination. 24,25 Within patient studies though largely uncommon has been documented in the field of Dermatology due to the superficial nature of the lesions as well as the use of topical treatment which are often unlikely to have a systemic effect. A randomized, double-blind, activecontrolled within patient design was used to compare the effectiveness of Fenticonazole (2%) cream b.i.d.…”
Section: Discussionmentioning
confidence: 99%